On single use plastic straws: Pre-ban findings on touristic beaches in Crete. (October 2021) - Fanini, Lucia; Guittard, Alice
Abstract: This baseline intends to report on littering related to single-use plastic straws, contextualized on two touristic beaches on the Northern shores of Crete (Greece). While beached straws were found to be mainly depending on local drivers, the study further highlighted an additional source of pollution related to plastic straws: the clear wrap in which single-use items can be offered to users. Over the summer months, a number of discarded straw wraps was in fact found, significantly related to both beach width and the presence of colorful straws. Wraps are different in shape, material, as well as likelihood of being dispersed and broken down in the environment, and easily escape estimates from non-targeted sampling. The ban on single use items seems then to be the most effective approach to avoid straws and, indirectly, straw wraps litter or spills. Graphical abstract: Unlabelled Image Highlights: Plastic straws were collected on touristic beaches over a summer season before the ban. Analyses of similarity highlighted informative items, including straw clear wraps. Increasing beach width was related to higher findings of all kinds of straws. Clear wraps were identified as relevant straw-related item, though usually overlooked.